DATA-DRIVEN MANAGEMENT IN IMPROVING LEARNING QUALITY - Hansen Lutfiartha; Endang Wuryandini; Muhtarom (SOSIOEDUKASI, 2026)
Although regulations regarding data-driven planning have been established, implementation in the field often faces challenges where data use tends to be limited to administrative fulfillment and has not been fully integrated with school management functions. This study aims to analyze the integration of management functions of planning, organizing, implementing, and controlling data-driven planning as a strategic mechanism for improving the quality of learning. Using a qualitative approach with a case study design at SMP Negeri 2 Taman, research informants were determined using a purposive sampling technique involving the principal, curriculum development team, teachers, school administration, and the school committee. Data was collected through interviews, observations, and document analysis. The results showed that the school successfully synergized management functions with the Identification, Reflection, and Improvement cycle. Planning used the Education Report to identify priority problems, organizing utilized data reflection for role allocation, implementation was realized through In-House Training programs and learning communities, and control was carried out through periodic monitoring and evaluation. It was concluded that data-driven management is effective only if supported by teacher data literacy and leadership capable of transforming data into real pedagogical interventions, not just a document formality.